Fast Transient Simulations From S-Parameters With Improved Reference Impedance - Khairulzaman, Mohd Ridzuan (2015)

(untitled)
As a design becomes more sophisticated, analyzing it becomes more complicated, and supporting high data speeds and high operating frequencies becomes more challenging. Conventional transient simulation can be a troublesome and a computationally expensive procedure, as the process takes a long time to complete. Hence, a fast transient simulation is utilized based on scattering parameter (S-parameter) convolution. This alternative approach to the S-parameter offers stability, efficiency and robust computation. In this research, the S-parameter frequency domain convolution was presented, which was later converted to impulse response or time domain data using the inverse Fast Fourier Transform (IFFT) algorithm for the fast transient simulation of multiport interconnect network or typically addressed as a black box model. Subsequently, the S-parameter convolution can be further improved by optimizing the reference system of the model. An improvement by 64% and 29.5% of IFFT point usage numbers with Black Box 1 and Black Box 2. These results respectively were obtained based on optimal reference impedance assigned in S-parameter synthesis on black box models, thus speeding up the convolution program, compared to the nominal reference impedance of 50Ω used to perform the fast transient simulation. Besides, the optimization routine implemented on the design has smoothed the magnitude of the waveform and there is no significant effect observed on the time domain response.